INDIAN PENAL CODE/ by C. K. Thakker (Takwani), Former Judge, Supreme Court of India, (NATIONAL CAPITAL LAW JOURNAL, 2021)
NA
Keywords: Indian Penal Code (IPC); Law; Criminal Law; General Principles of Criminal Law; Specific Offences; Supreme Court Judgments; Law Commission Reports; Criminal Procedure